Meibomian Gland Carcinoma Masquerading As A Giant Chalazion – A Case Report - Trivedi, Stuti N; Trivedi, Nitin V.; Khandekar, Rajiv (Archives of Clinical and Medical Case Reports, 2020)
A 50-year-old male presented with a non-tender mass on the left eye upper lid that gradually increased in six months. There was no history of trauma, other tumor or surgery. With clinical diagnosis of giant chalazion incision drainage and curettage was performed. Tumor recurred at the same place after 3 months. Meibomian gland carcinoma was suspected, excised in Toto and lid was reconstructed. Histopathology of biopsy material revealed adenocarcinoma of Meibomian gland. This rare presentation of adnexal malignancy could be missed and therefore author recommend biopsy of all lid lesion when operated.